Calcium in peroxisomes: An essential messenger in an essential cell organelle - Sargsyan, Yelena; Kalinowski, Julia; Thoms, Sven (Frontiers in Cell and Developmental Biology, 2022)
Calcium is a central signal transduction element in biology. Peroxisomes are essential cellular organelles, yet calcium handling in peroxisomes has been contentious. Recent advances show that peroxisomes are part of calcium homeostasis in cardiac myocytes and therefore may contribute to or even shape their calcium-dependent functionality. However, the mechanisms of calcium movement between peroxisomes and other cellular sites and their mediators remain elusive. Here, we review calcium handling in peroxisomes in concert with other organelles and summarize the most recent knowledge on peroxisomal involvement in calcium dynamics with a focus on mammalian cells.